Non-cancer effects after proton beam therapy for pediatric tumors- a narrative review - Zając-Grabiec, Anna; Biesaga, Beata; Krzyżowska, Monika; Drosik-Rutowicz, Katarzyna; Miszczyk, Justyna (Frontiers in Oncology, 2025)
IntroductionRadiation therapy can cause serious complications and side effects, especially in children. Proton beam therapy is considered as safer and more effective than traditional photon therapy because this type of modality offers precise radiation dose delivery to cancer cells while minimizing irradiation dose to adjacent normal tissue. Moreover, pediatric patients undergoing PBT may also experience a range of non-cancer late effects, including brainstem injury, cognitive dysfunctions, and side effects from endocrine or cardiovascular systems. The present type and frequency of non-cancer effects in children after proton therapy.MethodsTherefore, this review aims to analyze publications addressing the occurrence of side effects from proton therapy in pediatric patients, excluding those related to the induction of secondary malignancies. We used data from two publicly available databases for this review: the U.S. National Library of Medicine’s ClinicalTrials.gov (https://clinicaltrials.gov) for the analysis of clinical trials and PubMed, utilizing iCite (https://iCite.od.nih.gov)/Office of Portfolio Analysis, NIH, Bethesda, MD), a web-based application providing access to bibliometric information on publications.ResultsThe review of the literature shows that PBT reduces the risk of cognitive, neuroendocrine, and cardiovascular dysfunctions concerning those observed after PT. Contradictory results were observed for brain stem injury. The majority of studies found cumulative incidence (CI) of brainstem injury at a relatively low level (0.7% – 5.0%) after PBT, as compared to PT.DiscussionHowever, some authors underlie a higher rate of brainstem injury in children irradiated due to tumors localized in PF. Therefore, further studies, especially prospective ones, are needed to accurately describe the incidence and risk of late toxicity of proton beam therapy in children.